Determination of metals: nickel, chromium, copper, zinc and cadmium (Ni, Cr, Cu, Zn And Cd) in crude oil samples / Nensirati binti Supahan - Supahan, Nensirati (2014)
Samples of crude oil from two different oil fields, North Lukut and Penara, off shore of Terengganu, Malaysia were analyzed for trace metals: cadmium, chromium, copper, nickel and zinc. There were five crude oil samples from North Lukut oil field and three crude oil samples from Penara. All of the crude oil samples were from different wells and undergo sample preparation via wet digestion by using mixture of concentrated acids which were sulphuric acid, nitric acid and hydrochloric acid. The digested crude oil samples were then analyze by atomic absorption spectrometry (AAS) analysis. The results showed that the highest concentration of trace metals was zinc which read 1.562 ppm in North Lukut A-2 sample whereas the lowest concentration of trace metals is copper which was 0.095 ppm in Penara A-5L sample. It was reported that the concentration of the trace metals in the North Lukut and Penara crude oil samples were lower than the average concentration of crude oils as reported by Petroleum High Production Volume Testing Group by the American Petroleum Institute (API). However, despite their low concentration, the trace metals can still be detrimental to refinery operations and the environment and therefore, should be removed before refining.